Analisis Break Even Point (Bep) Usaha Pembibitan Semangka Di CV Nusantara Group Kecamatan Gunung Sugih, Kabupaten Lampung Tengah, Provinsi Lampung - Selvita, Aggnes Listy; Listiyani, Listiyani; Sayekti, Agatha Ayiek Sih (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The aims of the study: 1) to determine the growth in acceptance and profits of the watermelon nursery business in CV. Nusantara Group in 2019 - 2022; 2) to find out BEP (production BEP, price BEP, and acceptance BEP); 3) to determine the sensitivity value of production BEP and acceptance BEP to changes in prices and production costs. The basic research method used is descriptive method by collecting data compiled and analyzed. The location determination method uses purposive sampling by choosing a location deliberately based on the business that carries out watermelon nurseries. The data analysis used is quantitative analysis with break even point and profit data analysis methods. The results show that the highest revenue growth will occur in 2022 (41%), the highest profit growth will occur in 2021 (130%). The lowest production BEP occurred in 2021 (164.086 seeds), 2021 price BEP (Rp. 1.490/seed), 2021 revenue BEP (Rp. 278.946.844). The selling price sensitivity decreased (5%), the production BEP increased (17%) and revenue BEP increased (11%). While the sensitivity of production costs increased (5%), production BEP increased (16%) and revenue BEP increasedÂ (16%).